2013
DOI: 10.2754/avb201382020219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tramadol with tiletamine/zolazepam-xylazine as anaesthesia in cats

Abstract: This study was conducted to investigate the effect of the combination of tiletamine/zolazepamxylazine-tramadol (TZXT) in cats and to compare its efficacy as an anaesthetic technique with tiletamine/zolazepam-xylazine (TZX). Fourteen healthy thirteen-month-old cats of both sexes were immobilized by TZXT or TZX on two different occasions. The cats' scores for immobilization, analgesia and baseline physiological indicators, heart rate, respiratory rate and rectal temperature, were recorded before and 5, 10, 15, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Under normal circumstances, ketamine has few cardiopulmonary side effects; it does not inhibit the cardiovascular or respiratory system and has significant analgesic effect (3,7,14). Tramadol caused no significant additional respiratory depressant effect in cats (11). Our results showed that RR and SpO 2 in all treatments were not changed significantly compared with baseline, and the changes in RR and SpO 2 remained within clinically acceptable limits in all period of anesthesia.…”
Section: Tab 2 Mean ± Sd Values For Physiological Parameters Evaluated In Cats Anaesthetized With Two Combinations Of Anaesthetic Drugsmentioning
confidence: 50%
See 1 more Smart Citation
“…Under normal circumstances, ketamine has few cardiopulmonary side effects; it does not inhibit the cardiovascular or respiratory system and has significant analgesic effect (3,7,14). Tramadol caused no significant additional respiratory depressant effect in cats (11). Our results showed that RR and SpO 2 in all treatments were not changed significantly compared with baseline, and the changes in RR and SpO 2 remained within clinically acceptable limits in all period of anesthesia.…”
Section: Tab 2 Mean ± Sd Values For Physiological Parameters Evaluated In Cats Anaesthetized With Two Combinations Of Anaesthetic Drugsmentioning
confidence: 50%
“…However, this degree of decline does not adversely affect the body. It has been reported that tramadol has no significant cardiovascular inhibitory effect on cats (11). Therefore, the effects of KDZT and KDZ on the heart can be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, considering the ease of administration of medications in the case of cats and the comfort of the animal with respect to handling and environment, intramuscular injection of Tiletamine-zolazepam combination @ 8 mg/kg could be recommended as an excellent inducing agent providing quick rapid and smooth induction of anaesthesia in cats allowing easy intubation Fig 1. The effect of an inducing agent over skeletal muscle relaxation was based on a modified scale score given by Li et al (2013) which from 0 to 3, where score 0 being resistant to anaesthetic and 3 representing the most profound relaxation of muscles. The mean±S.E score for muscle relaxation was 2.6±0.14 in group A and 2.4±0.14 in group B with the cat exhibiting profound jaw relaxation and easy intubation.…”
Section: Resultsmentioning
confidence: 99%